Adoptive Cell Transfer of Regulatory T Cells Exacerbates Hepatic Steatosis in High-Fat High-Fructose Diet-Fed Mice - Van Herck, Mikhaïl A.; Vonghia, Luisa; Kwanten, Wilhelmus J.; Vanwolleghem, Thomas; Ebo, Didier G.; Michielsen, Peter P.; De Man, Joris G.; Gama, Lucio; De Winter, Benedicte Y.; Francque, Sven M. (Frontiers in Immunology, 2020)
Background and aims: Non-alcoholic steatohepatitis (NASH) is a multisystem condition, involving the liver, adipose tissue, and immune system. Regulatory T (Treg) cells are a subset of T cells that exert an immune-controlling effect. Previously, a reduction of Treg cells in the visceral adipose tissue (VAT) was shown to be associated with a more severe degree of liver disease. We aimed to correct this immune disruption through adoptive cell transfer (ACT) of Treg cells. Methods: Male 8-week-old C57BL/6J mice were fed a high-fat high-fructose diet (HFHFD) for 20 weeks. Treg cells were isolated from the spleens of healthy 8 to 10-week-old C57BL/6J mice and were adoptively transferred to HFHFD-fed mice. PBS-injected mice served as controls. Plasma ALT and lipid levels were determined. Liver and adipose tissue was assessed histologically. Cytotoxic T (Tc), Treg, T helper (Th) 1 and Th17 cells were characterized in VAT, liver, subcutaneous adipose tissue (SAT), blood, and spleen via flow cytometry. Gene expression analysis was performed in SAT and VAT of mice fed either the HFHFD or a control diet for 10-32 weeks. Results: ACT increased Treg cells in SAT, but not in any of the other tissues. Moreover, the ACT induced a decrease in Th1 cells in SAT, liver, blood, and spleen. Higher plasma ALT levels and a higher degree of steatosis were observed in ACT mice, whereas the other HFHFD-induced metabolic and histologic disruptions were unaffected. Expression analysis of genes related to Treg-cell proliferation revealed a HFHFD-induced decrease in all investigated genes in the SAT, while in the VAT the expression of these genes was largely unaffected, except for a decrease in Pparg. Conclusion: ACT of Treg cells in HFHFD-fed mice exacerbated hepatic steatosis, which was possibly related to the increase of Treg cells in the SAT and/or the general decrease in Th1 cells. Moreover, the HFHFD-induced decrease in Pparg expression appeared critical in the decrease of Treg cells at the level of the VAT and the inability to replenish the amount of Treg cells by the ACT, while the mechanism of Treg cell accumulation at the level of the SAT remained unclear.